KAJIAN RANCANG BANGUN SOLAR WATER HEATER (SWH) ANALISIS TERHADAP KOEFISIEN LAJU KONVEKSI DAN EFISIENSI PEMANASAN AIR - Ridwan, Kiagus Ahmad (Politeknik Negeri Sriwijaya, 2019)
We know that, solar energy can be used as an alternative source. One of them is by converting solar energy into heat energy using solar collectors, which are called solar water heaters. In this study a solar radiation heat absorbent device was used to heat water using copper pipes and aluminum pipes. This study aims to obtain the need for pipe length, find out the heat used to heat water, and analyze the effect of radiation intensity on the heating efficiency of the water produced. This water heater is made through several preparation stages such as literature study, consultation with mentors, tool making, and also final analysis and reporting. With a pipe length of 5 meters and a diameter of 0,5 inch, with the provisions of batch flow at intervals of every 10 minutes, the results of the research shows that the value of useful energy for heating the largest water occurs in the copper pipe is 32,65Btu and an energy loss of 80,33Btu. It can be seen that the greater the intensity of solar radiation, the greater the rate of convection, useful energy, and the efficiency of water heating. With the largest convection rate (h) in aluminum pipes that is 750,4w/m2oc at radiation intensity of 895w/m2 and efficiency of 40,52%. While the largest convection rate (h) in copper pipes is 818,6w/m2oc at a radiation intensity of 889,7w m2 and efficiency of 54,93%